Cascade Nonlinear Control for a Class of Cascade Systems∗. Issue 8 (2015) - García-Sandoval, J.P.; Dochain, D.; González-Álvarez, V.
Abstract: By combining nonlinear control theory and constructive analysis, we address the control of dynamical systems with a cascade structure where the first subsystem is connected in series with the second subsystem, while the input acts in parallel on both subsystems, which may exhibit multiple steady states with bistable behavior, typically undesired in practice due to safety or operational conditions. The resulting regulation scheme is a cascade control structure which stabilizes the second subsystem within a desired region of the state space while guaranteeing the output regulation in the first subsystem. The performance of the proposed control is evaluated and compared to nonlinear single-input-single-output controllers in a simulation example of a chemical reaction taking place in two reactors connected in series.